Heavenly journeys, earthly concerns : the legacy of the miʻraj in the formation of Islam - Vuckovic, Brooke Olson (Routledge, 2005)
Examines how an elite group of traditionists, historians and theologians shaped Muslims' perceptions of their prophet, their community and their behaviour by retelling and interpreting the story of Muhammad's ascent to heaven (the mi'raj).
Keywords: Muḥammad, -- Prophet, -- -632 -- Isrāʼ and Miʻrāj.; Muḥammad, -- Prophet, -- -632 -- Anecdotes.; Mahomet, -- le prophète, -- -632 -- Isrā' et Miʻrāj.; Muḥammad, -- Prophet, -- -632; Muḥammad, -- ca.570-632.; Islam -- Origin.; Ummah (Islam); Electronic books.; Islam -- Origines.; Livres numériques.; e-books.; 11.82 Islamic traditional literature.; RELIGION -- Islam -- General.; Islam -- Origin; Anecdotes